PELATIHAN DAN PENERAPAN GOOD AGRICULTURAL PRACTICES DALAM BUDIDAYA SAYURAN DI YAYASAN NUR AL-MU’MIN, PONTIANAK, KALIMANTAN BARAT - Yama, Danie Indra; Fakhrudin, Jaini; Muliani; Zaenal Mutaqin; Tika Rahma Yunita; Rista Delyani; Muhammad Ali; Mardoyo (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
The Nur Al-Mu'min Foundation Center in Kubu Raya covers an area of 3 hectares. The land is currently used for a mosque, kindergarten buildings, and Al-Qur'an education facilities. Around the mosque area, there is still vacant land that tends to be unproductive, even though it has the potential to generate income for the foundation. The goal of this PPM program is to improve partners' skills in managing non-productive land by cultivating vegetables using the GAP (Good Agricultural Practices) system. By implementing the GAP system, unproductive land can become productive, vegetable harvests can be sold, and land management can be carried out effectively. The PPM activities begin with an introduction to the foundation, followed by outreach activities, hands-on field practice, partner mentoring, and an evaluation after harvesting the crops. The impact of the community service program is assessed using a questionnaire filled out before and after participation in the activity. The pre-activity questionnaire results showed that 90.91% of participants had never heard of GAP, but all participants were interested in learning about it, as they found it useful and beneficial for vegetable cultivation. The post-activity questionnaire results indicated an increase in both knowledge and skills among participants, with 66.67% expressing willingness to share their knowledge with the surrounding community. — Pusat kegiatan Yayasan Nur Al-Mu’min yang berada di Kubu Raya memiliki lahan seluas 3 hektar. Lahan tersebut saat ini baru dimanfaatkan sebagai lokasi bangunan masjid, gedung TK dan TPA. Di sekitar wilayah masjid masih terdapat lahan kosong yang cenderung tidak produktif, sementara lahan tersebut dapat dimanfaatkan untuk menambah penghasilan atau pemasukan bagi yayasan. Tujuan dari pelaksanaan PPM ini adalah meningkatkan keterampilan mitra dalam pengelolaan lahan non produktif melalui budidaya sayuran dengan sistem Good Agricultural Practices. Lahan kosong menjadi produktif, hasil budidaya sayuran dapat dijual, serta pengolahan lahan dapat dilakukan dengan baik melalui sistem GAP. Kegiatan PPM dimulai dengan pengenalan Yayasan dan dilanjutkan dengan kegiatan penyuluhan, praktik di lapangan, pendampingan terhadap mitra dan evaluasi kegiatan yang dilakukan setelah selesai panen hasil tanaman. Setelah dilakukan penyuluhan serta praktik langsung di lapangan, baik dari segi pengetahuan ataupun keterampilan meningkat. Kegiatan penyuluhan diisi dengan penekanan materi mengenai pengelolaan lahan, benih, pemupukan, pengairan dan peserta antusias dalam mengikuti penyuluhan. Kegiatan praktik ditekankan pada pengolahan lahan, budidaya sayuran sesuai GAP dan meninggalkan budidaya sayuran secara turun menurun. Semua peserta juga akan mengaplikasikan GAP pada budidaya sayuran yang akan mereka lakukan.